Precision surgery and genitourinary cancers. Issue 5 (May 2017) - Autorino, R.; Porpiglia, F.; Dasgupta, P.; Rassweiler, J.; Catto, J.W.; Hampton, L.J.; Lima, E.; Mirone, V.; Derweesh, I.H.; Debruyne, F.M.J.
Abstract: The landscape of the surgical management of urologic malignancies has dramatically changed over the past 20 years. On one side, better diagnostic and prognostic tools allowed better patient selection and more reliable surgical planning. On the other hand, the implementation of minimally invasive techniques and technologies, such as robot-assisted laparoscopy surgery and image-guided surgery, allowed minimizing surgical morbidity. Ultimately, these advances have translated into a more tailored approach to the management of urologic cancer patients. Following the paradigm of "precision medicine", contemporary urologic surgery has entered a technology-driven era of "precision surgery", which entails a range of surgical procedures tailored to combine maximal treatment efficacy with minimal impact on patient function and health related quality of life. Aim of this non-systematic review is to provide a critical analysis of the most recent advances in the field of surgical uro-oncology, and to define the current and future role of "precision surgery" in the management of genitourinary cancers.